2015
DOI: 10.1021/acs.jpcc.5b07132
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Band Gap of CH3NH3PbI3 Stabilized with PMMA: A Modulated Surface Photovoltage Study

Abstract: CH 3 NH 3 PbI 3 layers chemically stabilized with poly(methyl methacrylate) (PMMA), relevant for photovoltaic applications, have been investigated by modulated surface photovoltage (SPV) spectroscopy at temperatures (T) between −182 and 60 °C. SPV is sensitive only to the PMMA/CH 3 NH 3 PbI 3 interface region where photogeneration and charge separation take place. The T dependencies of the Tauc gap (E g-Tauc , equivalent to absorption measurements) and of the gap determined from the maximum slope (E g-tp , alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 28 publications
9
57
0
Order By: Relevance
“…This mechanism seems to be consistent with our findings of phase transition inhibition in 1D and the decreasing phase transition temperature in 2D, as well as providing a mechanical origin to the structural phase transition in 3D. 69 Notice also a recent report about the possibility of phase transition inhibition in thin films of perovskites stabilized with PMMA, 70 a result that might also be attributed to interfacial stress.…”
Section: Discussionsupporting
confidence: 91%
“…This mechanism seems to be consistent with our findings of phase transition inhibition in 1D and the decreasing phase transition temperature in 2D, as well as providing a mechanical origin to the structural phase transition in 3D. 69 Notice also a recent report about the possibility of phase transition inhibition in thin films of perovskites stabilized with PMMA, 70 a result that might also be attributed to interfacial stress.…”
Section: Discussionsupporting
confidence: 91%
“…However, the linear dependencies in the inset and their tangents are similar to those of other perovskite materials, e.g. polycrystalline tetragonal and cubic phases of MAPI 3 , MAPbI 3-x Br x and MAPbI 3-x Cl x [17,22], powders of orthorhombic, tetragonal, and cubic phases of MAPbBr 3 and FAPbBr 3 [23], and polycrystalline films of CsSnI 3 [24]. …”
Section: Photoluminescencementioning
confidence: 71%
“…Furthermore, the phase shifted by 90 • signal was smaller in magnitude compared to in-phase signal. This suggests that trapping and de-trapping of charge carriers may lead to a slow response of the SPV spectra [18]. Since in-phase and phase shifted by 90 • signals had the same signs, charge separation was caused by the two mechanisms of charge separation and that relaxation of SPV signals was due to recombination processes [24].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Dittrich et al reported on the temperature dependence of the band gap of CH 3 NH 3 PbI 3 stabilized with PMMA using SPV and observed a jump in the band gap at 40 • C corresponding to transition from the tetragonal to cubic phase. In contrast, there was no signature in the band gap for transition from the tetragonal to orthorombic phase and concluded that there were structural interactions between CH 3 NH 3 PbI 3 and PMMA interfaces [18]. Charge transport properties and structural properties between perovskite and PMMA were investigated using modulated surface photovoltage spectroscopy (SPV), photoluminescence (PL), and grazing incidence X-ray diffraction (GIXRD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation